CAOS Coach 2006 Simulation Team: An Opponent Modelling Approach - Iglesias, J. A.; Ledezma, A.; Sanchis, A. (COMPUTING AND INFORMATICS, 2012)
Agent technology represents a very interesting new means for analyzing, designing and building complex software systems. Nowadays, agent modelling in multi-agent systems is increasingly becoming more complex and significant. RoboCup Coach Competition is an exciting competition in the RoboCup Soccer League and its main goal is to encourage research in multii-agent modelling. This paper describes a novel method used by the team CAOS (CAOS Coach 2006 Simulation Team) in this competition. The objective of the team is to model successfully the behaviour of a multi-agent system.